Study on uniaxial compression mechanical properties of 3D printed columnar joint test blocks - Zhenbo Xu; Zhende Zhu; Chao Jiang (Scientific Reports)
Abstract The columnar joint skeleton of 3D printed Acrylonitrile Butadiene Styrene (ABS) material, the skeleton of cement mortar and ultraviolet aging treatment are combined to pour the columnar joint rock mass (CJRM) test block. The strength, deformation, energy and failure modes of the specimens with different dip angles were analyzed by uniaxial compression test. The influence of joint skeleton on the strength of the test block was analyzed. The effect of aging time on ABS parameters was evaluated. The results show that the uniaxial compressive strength and elastic modulus are ' U ' type with the increase of dip angle, the elastic strain energy is ' V ' type, and the dip angle of 45° is the minimum value. The four failure modes are: shear failure, splitting failure, shear tensile mixed failure, shear splitting mixed failure. The anisotropy of CJRM is extremely high. The skeleton reduces the strength and elastic modulus of the solid test block, and has the greatest influence on the strength of the test block with dip angle of 75°. With the increase of aging time, the strength and deformation parameters of ABS decreased, and the yellowness index and infrared spectrum peak area increased.